Pharmacological activity of South African medicinal plants and mechanism of action against Staphylococcus aureus isolated from clinical bovine mastitis - McGaw, Lyndy Joy (University of Pretoria, 2024)
Thesis (PhD (Paraclinical Sciences))--University of Pretoria, 2023.